2021
DOI: 10.3174/ajnr.a7264
|View full text |Cite
|
Sign up to set email alerts
|

Local Intra-arterial Thrombolysis during Mechanical Thrombectomy for Refractory Large-Vessel Occlusion: Adjunctive Chemical Enhancer of Thrombectomy

Abstract: BACKGROUND AND PURPOSE: Data on adjunctive intra-arterial thrombolysis during mechanical thrombectomy for refractory thrombus are sparse. The aim of this study was to evaluate the efficacy and safety of local intra-arterial urokinase as an adjunct to mechanical thrombectomy for refractory large-vessel occlusion. MATERIALS AND METHODS:We retrospectively evaluated patients with acute ischemic stroke who underwent mechanical thrombectomy for anterior circulation large-vessel occlusion between January 2016 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…A previous meta-analysis including 4581 patients by Chen et al 10 reported that IA treatment (thrombolytics or glycoprotein IIb/IIIa inhibitors) was associated with a higher rate of functional independence and another meta-analysis including 2797 patients by Kaesmacher et al 11 reported that IAT was not associated with higher rates of functional independence as an adjunct to MT. Inclusion of additional studies 5,[12][13][14][15][16][17] such as results from the randomized CHOICE 17 trial in our analysis increased the sample size (7572 patients) by almost 2-4 folds compared with the previous analyses by Chen et al 10 and Kaesmacher et al 11 Therefore, the precision of estimates of various outcomes was higher, and type 2 errors in comparisons were reduced. By increasing the design diversity among included studies, we also identified the prominent effect of design and quality of the studies on the association between IAT and functional independence at 90 days.…”
Section: Salient Findingsmentioning
confidence: 77%
See 3 more Smart Citations
“…A previous meta-analysis including 4581 patients by Chen et al 10 reported that IA treatment (thrombolytics or glycoprotein IIb/IIIa inhibitors) was associated with a higher rate of functional independence and another meta-analysis including 2797 patients by Kaesmacher et al 11 reported that IAT was not associated with higher rates of functional independence as an adjunct to MT. Inclusion of additional studies 5,[12][13][14][15][16][17] such as results from the randomized CHOICE 17 trial in our analysis increased the sample size (7572 patients) by almost 2-4 folds compared with the previous analyses by Chen et al 10 and Kaesmacher et al 11 Therefore, the precision of estimates of various outcomes was higher, and type 2 errors in comparisons were reduced. By increasing the design diversity among included studies, we also identified the prominent effect of design and quality of the studies on the association between IAT and functional independence at 90 days.…”
Section: Salient Findingsmentioning
confidence: 77%
“…The quality of included observational studies 5,6,[12][13][14][15][16][20][21][22][25][26][27][28][29][30][31] was assessed by three independent reviewers (A.L., I.N.A., and D.K.) for risk of bias using the Newcastle-Ottawa Quality Scale (NOS) for Cohort Studies.…”
Section: Risk Of Bias Assessment In Studiesmentioning
confidence: 99%
See 2 more Smart Citations